sec teta + tan teta = x
prove that
![\frac{ {x}^{2} - 1 }{ {x}^{2} + 1} = \sin(teta) \frac{ {x}^{2} - 1 }{ {x}^{2} + 1} = \sin(teta)](https://tex.z-dn.net/?f=+%5Cfrac%7B+%7Bx%7D%5E%7B2%7D+-+1+%7D%7B+%7Bx%7D%5E%7B2%7D++%2B+1%7D++%3D++%5Csin%28teta%29+)
Answers
Answered by
0
Answer:
sec teta + tan teta = x
prove that
Step-by-step explanation:
please follow me and please make brilliant me
Answered by
2
Answer:
Nanum tamil than stylishthamilachi
Step-by-step explanation:
Bio la irukathu nejam than.
Similar questions
Math,
3 months ago
Biology,
3 months ago
Physics,
3 months ago
Math,
7 months ago
English,
7 months ago
Social Sciences,
1 year ago
Computer Science,
1 year ago